2019
DOI: 10.1002/brb3.1414
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous nonataxic phenotypes of spinocerebellar ataxia in a Taiwanese population

Abstract: Background Spinocerebellar ataxia (SCA) presents with variable clinical presentations in addition to ataxia. The aim of this study was to reappraise the diverse nonataxic clinical characteristics of the five most common SCA subtypes in the Asian population. Methods The clinical presentations of 90 patients with genetically confirmed SCA1, SCA2, SCA3, SCA6, or SCA17 were assessed retrospectively between November 2008 and September 2018 at a tertiary referral center in Taiwan. Results Parkinsonism was the most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Mean Age of Examination (in years) of recruited cases has been listed in Table 1. On evaluation of SCA positive patients' ages (at examination), it is observed that SCA2 is prevalent in younger population (18-29 years); SCA12 in elder age group (50)(51)(52)(53)(54)(55)(56)(57)(58)(59) and other SCA types in middle age group (30-49) (Figure 2).…”
Section: Age Distribution Of Patientsmentioning
confidence: 99%
“…Mean Age of Examination (in years) of recruited cases has been listed in Table 1. On evaluation of SCA positive patients' ages (at examination), it is observed that SCA2 is prevalent in younger population (18-29 years); SCA12 in elder age group (50)(51)(52)(53)(54)(55)(56)(57)(58)(59) and other SCA types in middle age group (30-49) (Figure 2).…”
Section: Age Distribution Of Patientsmentioning
confidence: 99%
“…Genomic DNA was isolated from 10 mL of venous blood from all participants, following a standard protocol. Trinucleotide repeat expansions at the SCA1, 2, 3, 6, 17 and DRPLA genes were excluded from all participants, following the methods described previously [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recent advances in genetic studies have identified more than 40 genes causing distinct subtypes of SCA [ 14 ]. We and other groups have previously described the clinical features of Taiwanese patients with the most common genetic causes of SCA [ 15 , 16 ]. To extend our knowledge of the genetic architecture and pathophysiology of SCA in our population, we performed whole-genome sequencing (WGS) and comparative analysis in a genetically undiagnosed multiplex family with SCA.…”
Section: Introductionmentioning
confidence: 99%
“…We continued our literature search for Asia-specific phenotypic aspects using a citation-based search, rather than an additional broad literature search as we expected that it would result in a rather small selection of studies. Two recent studies were used as a starting point [4,5]. Other studies suggesting Asia-specific elements within a SCA subtype were reviewed and included.…”
Section: Methodsmentioning
confidence: 99%
“…However, only a few Asian studies have actually reported on the frequency of parkinsonism or other movement disorders in SCAs. A Taiwanese study found that parkinsonism was the most common non-ataxic manifestation (21.1%) in a cohort of 90 SCA1, SCA2, SCA3, SCA6, and SCA17 patients [5]. Studies from other Asian countries reported a lower prevalence of parkinsonism.…”
Section: Part Ii: Phenotypic Differences Compared To Other Continents and Asia Specific Phenotypesmentioning
confidence: 99%